Hubungan antara overweight dengan kualitas hidup pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi - Dhio Kurnia Arung; Ronald Imanuel Ottay; Windy Mariane Virenia Wariki (Jurnal Kedokteran Komunitas dan Tropik, 2026)
Background: Overweight is a global health issue that affects an individual’s overall health and quality of life. University students, as a productive age group, are also vulnerable to this condition due to lifestyle changes commonly experienced during academic life. These include irregular eating patterns such as excessive consumption of fast food, low levels of physical activity due to demanding academic schedules, and high stress levels. Aim: To analyze the relationship between overweight and quality of life among students of the Faculty of Medicine, Sam Ratulangi University. Methods: This study employed a quantitative analytic observational approach with a cross-sectional design. Results:  A total of 207 students participated in this research. Among respondents with overweight or obesity, 51 had poor quality of life and 29 had good quality of life. Meanwhile, among respondents with underweight or normal body mass index, 54 reported poor quality of life and 73 reported good quality of life. Conclusion: There is a significant relationship between overweight and quality of life among medical students at the Faculty of Medicine, Sam Ratulangi University.